The Effectiveness of Physical Exercise on Level of Symptom and Quality of Life in Primary Dysmenorrhea in Adolescent in Denpasar - Ni Luh Nopi Andayani; Ari Wibawa; Indah Pramita; Suhita Apsari Pradnyandewi; Govinda Vittala (P3M Universitas 'Aisyiyah Surakarta, 2024)
Background: young women often experience various problems including pain during menstruation. Menstrual pain which is called dysmenorrhea is pain in the stomach or uterus, pain that occurs together with the onset of menstruation which occurs several hours to days. The incidence of primary dysmenorrhea will influence and have a major impact on the quality of life of these adolescents. Purpose: This study aims to prove the effectiveness of physical exercises in the form of abdominal stretching and core strengthening in reducing the degree of complaints and the quality of life of young women with primary dysmenorrhea in Denpasar Method: Research method with one pre-test design and post-test group design. The research was conducted at a private physiotherapist in Denpasar, Bali from September to August 2022. The sample consisted of 30 people who received physical exercises in the form of abdominal stretching and core strengthening. Results: The Wilcoxon Test showed different results before and after the intervention obtained a value (p <0.05) which means that there was a significant difference before and after the intervention in the degree of complaints and quality of life. Conclusion: Physical exercise is effective on the degree of complaints and quality of life in adolescents with primary dysmenorrhea in Denpasar